Categorie giuridiche, giusrealismo e neuroscienze. Sulla nozione di rule-following - Bombelli, Giovanni (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
The recent “fatal attraction” between law and neuroscience involves legal institutions as well as any fundamental categories underlying the legal experience and, in particular, the concept of rule-following. Starting from this perspective, the analysis both of some aspects of the legal realism (more precisely its Scandinavian articulation: Hägerström and Ross) and of the recent neuroscientific debate can be a good point of view. On the one hand this comparison highlights the analogies between the legal realism and the neuroscientific investigation as regards the methodological approach and the topics discussed, on the other the deeply different theoretical landscape and the heterogeneous conceptualization emerge. Through the discussion of any critical issues (i.e.: the deterministic model of law, the idea of collective intentionality, the nature of the legal sanction) raised by the comparison legal realism-neuroscience, the paper remarks the unavoidable philosophical-legal complexity of the concept of rule-following.